Gamifying and Mobilising Social Enquiry-based Learning in Authentic Outdoor Environments - Morris Siu-Yung Jong; To Chan; Ming-Tak Hue; Vincent W. L. Tam (Educational Technology & Society, 2018)
There has been increasing discussion among educators and researchers about harnessing the idea of gamification to enhance the current learning and teaching practices in school education. Leveraging the context-aware mobile technology and student-centred learning theories, we have developed a mobile application, Gamified Authentic Mobile Enquiry in Society (GAMES), to support students in conducting authentic outdoor enquiry-based learning in social humanities education. This paper reports the quasi-experimental study in which we evaluated the learning effectiveness of GAMES in terms of supporting students’ knowledge construction, in comparison with the conventional outdoor enquiry-based learning approach. It involved a total of 559 Grade-10 students from top, middle, and bottom academic-banding schools. Results indicated that, compared to the conventional approach, GAMES had different degrees of positive effects on the high, moderate, and low academic-achieving participants. This study not only provides grounds for a wider adoption of GAMES in social humanities education, but also makes a contribution to empirical evidence in the field by designing, implementing and evaluating gamified mobile learning in authentic outdoor contexts.